Kinematic and mechanical response of dry woven fabrics in through-thickness compression: Virtual fiber modeling with mesh overlay technique and experimental validation. (3rd May 2021) - Daelemans, Lode; Tomme, Brecht; Caglar, Baris; Michaud, Véronique; Van Stappen, Jeroen; Cnudde, Veerle; Boone, Matthieu; Van Paepegem, Wim
Abstract: The through-thickness compressive behavior of fabric reinforcements is crucial in liquid composite molding manufacturing processes. Predictive simulations of the compressive response are thus necessary to enable a virtual processing workflow. These are complex however, as the compressive behavior of the reinforcement fabrics is non-linear. Altough virtual fiber modeling has proven to be a strong kinematical tool, it cannot predict the compressive response due to the lack of bending stiffness in the virtual fibers. Here, we describe a solution that enables predictive compressive simulations through hybrid virtual fibers. It is based on an overlay mesh-element technique, combining both (i) finite elements that determine the in-plane fiber properties as well as (ii) finite elements that determine out-of-plane fiber bending. Using these hybrid virtual fibers, the through-thickness compression of a twill woven fabric ply is simulated and experimentally validated using both μCT-based as compliance-based measurements. Excellent agreement between simulation and experiment is obtained for the right set of input parameters. Graphical abstract: Image 1 Highlights: Bending stiffness of virtual fibers allows for a general textile mechanical modelling framework. Virtual fibers with both tensile and bending stiffness are developed using a mesh overlay technique. Model uses input parameters that are physics based. Compressive response of single fabric ply is experimentally validated through in-situ μCT measurements.